Research on technical and tactical features of major overseas opponents of Shiming Zou in Olympic preparations - Wang, D.; Zhu, Y.; Liu, C. (International Journal of Sports Science and Engineering, 2010)
Shiming Zou made history by earning the gold medal at the 2008 Beijing Olympics in the light flyweight division using his unique "piratelike" fighting style. With the development of boxing, an increasing number of world elite boxers have emerged in the light flyweight division and they have become the biggest obstacles for Chinese boxing. The present paper studied the technical and tactical features of Zou`s major opponent, Mongolian Purevdorj Serdamba. The research analyzed the condition and characteristics of his technical and tactical application in competitions to provide pertinent strategies and programs for Zou`s further preparations, promote Chinese coaching levels and capabilities and provide scientific foundation for the sustainable development of Chinese boxing.